Effects of saddle height on economy and anaerobic power in well-trained cyclists - Peveler, W. W.; Grenn, J. M. (The Journal of Strength and Conditioning Research, 2011)
In cycling, saddle height adjustment is critical for optimal performance and injury prevention. A 25-35° knee angle is recommended for injury prevention, whereas 109% of inseam, measured from floor to ischium, is recommended for optimal performance. Previous research has demonstrated that these 2 methods produce significantly different saddle heights and may influence cycling performance. This study compared performance between these 2 methods for determining saddle height. Subjects consisted of 11 well-trained (Vo2max = 61.55 ± 4.72 ml/kg/min) male cyclists. Subjects completed a total of 8 performance trials consisting of a graded maximal protocol, three 15-minute economy trials, and 4 anaerobic power trials. Dependent measures for economy (Vo2, heart rate, and rating of perceived exertion) and anaerobic power (peak power and mean power) were compared using repeated measures analysis of variance (a = 0.05). V?o2 was significantly lower (reflecting greater economy) at a 25° knee angle (44.77 ± 6.40 ml·kg-1·min-1) in comparison to a 35° knee angle (45.22 ± 6.79 ml/kg/min) and 109% of inseam (45.98 ± 5.33 ml/kg/min). Peak power at a 25° knee angle (1,041.55 ± 168.72 W) was significantly higher in relation to 109% of inseam (1,002.05± 147.65 W). Mean power at a 25° knee angle (672.37 ± 90.21 W) was significantly higher in relation to a 35° knee angle (654.71 ± 80.67 W). Mean power was significantly higher at 109% of inseam (662.86 ± 79.72 W) in relation to a 35° knee angle (654.71 ± 80.67 W). Use of 109% of inseam fell outside the recommended 25-35° range 73% of the time. Use of 25° knee angle appears to provide optimal performance while keeping knee angle within the recommended range for injury prevention.